PEMBUATAN PETUNJUK PRAKTIKUM PENENTUAN TRAYEK PH INDIKATOR ALAMI BERBASIS KEARIFAN LOKAL MASYARAKAT DUSUN TEKALONG - Engga, Mardinus; Masriani, Masriani; Enawaty, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine feasibility of practicum instructions based on the local wisdom of the Tekalong hamlet community on sub acidic material sub discussion of acid base indicators. Research on plants used as natural dyes by the people of Tekalong hamlet used a snowball sampling technique. The form of this research is Research and Development, according to Borg & Gall following the research steps, namely: (1) research and information gathering; (2) planning; (3) development of the initial form of the product; (4) initial field test; (5) product revisions; (6) main field test; (7) revision of operational products. This research uses indirect communication techniques with data collection tools in the form of questionnaires consisting of feasibility questionnaires (language, graphics, material) and student response questionnaires to practical instructions. The percentage of linguist scores was 87.12% (very high), graphic experts 85.19% (very high), and material experts 90.75% (very high). The percentage of assessment sheets for students responses to the initial field test and the main field trials were 87.63% (very high) and 90.67% (very high). Based on the data analysis, it can be concluded that the practicum instructions of the Tekalong hamlet community on the sub-acid acid material sub discussion of acid-base indicators are appropriate to be used and receive good responses (very high criteria) from students.Â Keywords : Practicum Intructions, Local Wisdom, Natural Dyes